The Dynamics of the North Atlantic Subpolar Gyre Introduces Predictability to the Breeding Success of Kittiwakes - Hátún, Hjálmar; Olsen, Bergur; Pacariz, Selma (Frontiers in Marine Science, 2017)
Since the open-ocean subpolar Atlantic is amongst the most predictable regions in the world, our results hold promise for predicting the general production to seabird populations over a large geographical region adjacent to the northern North Atlantic and the Arctic Mediterranean. Colonies of black-legged kittiwakes Rissa tridactyla in the North Atlantic have declined markedly since the mid-1990s, partly due to repeatedly failing breeding seasons. We show a close link between the breeding success of a kittiwake colony in the Faroe Islands and the subpolar gyre index. Successful breeding follows winters with an expanded subpolar gyre and, by inference, increased zooplankton abundances southwest of Iceland. The environmental conditions in the northwestern Atlantic during the non-breeding and pre-breeding seasons might therefore be important. Furthermore, the subpolar gyre dynamics might influence the local food abundance on the Faroe shelf during the breeding season.